Bilinear Numerical Analysis of the Structural Behavior of a Dental Implant Applied as a Biomaterial Carbon Fiber Reinforced Polyether-Ether-Ketone (CFR-PEEK): A Finite Element Analysis - Miguel Martinez-Mondragon; Guillermo Urriolagoitia-Sosa; Beatriz Romero-Ángeles; Juan C Pérez-Partida; Itzel M Cruz-Olivares; Guillermo Urriolagoitia-Calderón (Wolters Kluwer Medknow Publications, 2023)
Introduction: This research aims to compare the distribution of stresses and general displacements between different dental implant abutments against a healthy tooth, as well as the mechanical behavior of the carbon fiber-reinforced polyether-ether-ketone (CFR-PEEK) material under load conditions. Methods: A biomodel of a healthy tooth was implemented by computed tomography (CT), considering three essential parts of the tooth (enamel, dentin, and pulp). Three different dental abutments were produced using the SolidWorks computer program. Applying the finite element method (FEM), a numerical evaluation was performed by introducing a critical load of 550 N and then unloading it to 0 N taking into consideration the behavior of the material (titanium and CFR-PEEK) as bilinear, isotropic, and homogeneous. Results: The difference in stress and total displacement between the dental implant (titanium and CFR-PEEK) and the healthy tooth was significant, going from critical stress values of 1087 to 324 MPa. Conclusion: When removing the load from the CFR-PEEK material, it presented residual stresses because the material passed its elastic limit despite this, demonstrating a better mechanical behavior than titanium.